2022
DOI: 10.1172/jci.insight.155282
|View full text |Cite
|
Sign up to set email alerts
|

Machine-learning classification identifies patients with early systemic sclerosis as abatacept responders via CD28 pathway modulation

Abstract: The efficacy of abatacept in patients with early diffuse systemic sclerosis (dcSSc) was analyzed to test the hypothesis that patients in the inflammatory intrinsic gene expression subset would show the most significant clinical improvement. 84 participants with dcSSc were randomized to receive abatacept or placebo for 12 months. RNA-seq was performed on 233 skin paired biopsies at baseline, 3-and 6-months. Improvement was defined as a 5 point or >20% change in modified Rodnan skin score (mRSS) between baseline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…A randomized control trial failed to demonstrate efficacy of abatacept on skin thickening in patients with SSc ( 189 ), although recent analysis by intrinsic gene expression signatures seemed to show an effect in patients in the inflammatory subset ( 190 ). Preliminary results of a recent randomized control trial indicate efficacy of abatacept in a subgroup of patients with IMNM ( 191 ).…”
Section: Resultsmentioning
confidence: 99%
“…A randomized control trial failed to demonstrate efficacy of abatacept on skin thickening in patients with SSc ( 189 ), although recent analysis by intrinsic gene expression signatures seemed to show an effect in patients in the inflammatory subset ( 190 ). Preliminary results of a recent randomized control trial indicate efficacy of abatacept in a subgroup of patients with IMNM ( 191 ).…”
Section: Resultsmentioning
confidence: 99%
“…These may depend on the drug being tested. For example, further analysis of data from the abatacept trial [31 ▪ ] has shown that expression of the costimulation of the CD28 Family Reactome Pathway was increased in patients in the ‘inflammatory’ subset and that expression decreased with abatacept, suggesting that high baseline expression might predict treatment response. A posthoc analysis of the DesiReS trial [32 ▪ ] comparing rituximab to placebo (noting that this was not a study specifically of early dcSSc [33]), concluded that high CD19-positive cell counts were associated with improvement in mRSS with rituximab.…”
Section: Skin Involvement In Early Diffuse Cutaneous Systemic Sclerosismentioning
confidence: 99%